Fracture Propagation and Hydraulic Properties of a Coal Floor Subjected to Thick-Seam Longwalling above a Highly Confined Aquifer. (3rd July 2021) - Li, Shaodong; Fan, Gangwei; Zhang, Dongsheng; Zhang, Shizhong; Chen, Liang; Ren, Shang; Fan, Yibo
Abstract : The high-pressure and water-rich confined aquifer occurring in the Ordovician limestone sequence poses great threats to the routine production of underground longwall mining. Considering the intense cooperation of mining disturbance and water pressure, water-conducting fractures within a coal seam floor can connect the lower aquifer and upper goaf, and this hydraulic behavior is considered the root of water inrush hazard and water loss or contamination. In this paper, the panel 4301 of the Longquan coal mine serves as the case where the panel works closely above the floor with high water pressure. By the combination of physical and numerical modelling approaches, the variation characteristics of fracture development and volumetric strain of floor rocks subjected to mining disturbance are analyzed. A numerical computation model is constructed based on the volumetric strain-permeability equation obtained by curve fitting, and on such basis, the impacts of different mining parameters on floor rock permeability are studied. The results show that the floor rocks experience fracture generation, extension, and convergence procedures as the workface advances along the longitudinal direction, and fractures appearing in front of the workface are more developed. In the whole process of coal seam extraction, the volumetric strain profile exhibits " Λ " shape and an inverted saddle shape before and after overburden strata collapse. By controlling a single variable, the paper reveals that panel height is of greater impact on floor permeability changes than panel length and panel width.